Approaches to suffering at the end of life: the use of sedation in the USA and Netherlands. Issue 4 (14th September 2012) - Rietjens, Judith AC; Voorhees, Jennifer R; van der Heide, Agnes; Drickamer, Margaret A
Abstract : Background: Studies describing physicians' experiences with sedation at the end of life are indispensible for informed palliative care practice, but they are scarce. We describe the accounts of physicians from the USA and the Netherlands, two countries with different regulations on end-of-life decisions regarding their use of sedation. Methods: Qualitative face-to-face interviews were held in 2007–2008 with 36 physicians (18 from the Netherlands, 18 from the USA), including primary care physicians and specialists. We applied purposive sampling and conducted constant comparative analyses. Results: In both countries, the use of sedation was described in diverse terms, especially in the USA, and was often experienced as emotionally challenging. Respondents stated different and sometimes multiple intentions for their use of sedation. Besides alleviating severe suffering, most Dutch respondents justified its use by stating that it does not hasten death, while most American respondents indicated that it might hasten death but that this was justifiable as long as that was not their primary intention. While many Dutch respondents indicated that they initiated open discussions about sedation proactively to inform patients about their options and to allow planning, the accounts of American respondents showed fewer and less-open discussions, mostly late in the dying process and with the patient's relatives. Conclusions: The justification for sedation and the openness with which it is discussed were found to differ in the accounts of respondents from the USA and the Netherlands. Further clarification of practices and research into the effect and effectiveness of the use of sedation is recommended to enhance informed reflection and policy making.